(untitled) (Bangladesh Journal of Botany, 2019)
The antimicrobial activity of different extracts (methanolic, ethyl acetate, hot and cold water extracts) of Morchella esculenta against bacterial strains including Agrobacterium tumefaciens, Bacillus atrophaeus, Bacillus subtilis, Citrobactor freundii, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Staphyllococcus aureus, Staphyllococcus epidermidis, Pseudomonas aeruginosa and Xanthomonas oryzae and some fungal strains such as Trychophyton rubrum, Rhizopus stolonifer, Trichoderma citrinoviride, Aspergillus fumigatus and Alternaria alternata was evaluated. Disc diffusion assay was used for antibacterial activity and well diffusion method was applied for measuring the antifungal activities of different extracts. Hot water extract was found more effective against bacterial strains and produced maximum zone of inhibition of 90% against Bacillus atrophaeus at 3 mg/disc, while cold water extract showed strong activity against the majority of selected fungal strains; Trichophyton rubrum, Trichoderma citrinoviride and Alternaria alternata. Ethyl acetate extract of M. esculenta revealed least antimicrobial activities against the tested microbes.